Soluble urokinase plasminogen activator receptor (suPAR) as a biomarker of early pregnancy location and viability compared with hCG, progesterone and estradiol. (April 2020) - Friis Petersen, Jesper; Grynnerup, Anna García-Alix; Mitchell, Nikki Have; Løssl, Kristine; Sørensen, Steen; Lindhard, Anette; Friis-Hansen, Lennart; Pinborg, Anja; Nyboe Andersen, Anders; Løkkegaard, Ellen
Highlights: suPAR is a novel immunological biomarker of early pregnancy inflammation. In prediction of live birth, miscarriage or ectopic pregnancy, suPAR is unfeasible. Progesterone, estradiol and hCG are superior predictors of early pregnancy outcome. Progesterone is the best predictor irrespective of a 6 weeks' gestation milestone. Abstract: A circulating biomarker of early pregnancy outcome independent of ultrasonography and gestational age is a coveted goal. This study evaluated soluble urokinase plasminogen activator receptor (suPAR), a well-described marker of inflammation and immunological activation, for this purpose, and compared it with established early pregnancy biomarkers of the luteoplacental phase: progesterone, estradiol and hCG. We merged data from two prospective first trimester cohorts to conduct a case-control study comparing these analytes in women who had either a live birth, a miscarriage or an ectopic pregnancy. The ability to predict pregnancy location and viability was assessed by areas under the receiver operating characteristic curves (AUC). Comparing women irrespective of gestational age with a live birth, miscarriage or ectopic pregnancy showed significantly lower suPAR values in the latter group (2.4 vs. 2.4 vs. 2.0 μg/L, p = 0.032, respectively), as were all other analytes. Before 6 weeks' gestation, suPAR was significantly inferior to progesterone, estradiol and hCG in pregnancy location and viability prediction (in 124 pregnancies, suPAR AUClocation = 0.69 [CI: 0.54–0.83] and AUCviability = 0.58 [CI: 0.48–0.69], while progesterone AUClocation = 0.95 [CI: 0.87–1.00] and AUCviability = 0.84 [CI: 0.75–0.92]). After 6 weeks' gestation, suPAR prediction improved but was inferior to hCG, progesterone and estradiol (in 188 pregnanices, suPAR AUClocation = 0.71 [CI: 0.63–0.78] and AUCviability = 0.70 [CI: 0.63–0.78] compared with hCG AUClocation = 0.96 [CI: 0.93–0.99] and AUCviability = 0.96 [CI: 0.93–0.98]). Collectively, suPAR is less useful as a predictor of early pregnancy outcome than hCG, progesterone and estradol.